SPIRITUAL LEADERSHIP, AND SERVANT LEADERSHIP ON WORK ENGAGEMENT (STUDY ON PT COLOURED CABINETS IN JEPARA) - Sofiyana, Nurul; Mansyur, Anwar (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2024)
The purpose of this study is to investigate the impact of servant and spiritual leadership on work engagement. Sample used was a census and the total respondents were 134 at the company Pt. Colored Cabinet in Jepara. The analytical method used in this study uses statistics utilizing the SPSS for analysis Statistics 25 application. The study's findings demonstrate the beneficial impact that spiritual leadership has on work engagement. Servant Work engagement and leadership are positively correlated. In accordance with research results, researchers provide suggestions to companies to increase supervision in work involvement and ensure and comply with company regulations.